PENGARUH MEDIA SOSIAL TWITTER TERHADAP HUBUNGAN PARASOSIAL DAN KEPERCAYAAN K-POPERS KEPADA LAWAN JENIS PADA FOLLOWERS AKUN @indomyfess - Maura Salsabila; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Social media has become a very helpful platform for K-Popers in accessing all sources of information about their idols. This study aims to determine how much influence Twitter social media has on parasocial relationships and K-Popers trust in the opposite sex on followers of the @indomyfess account. This study uses a quantitative method using purposive sampling technique and using the Slovin formula which obtains a total sample of 400 from 224 thousand population of Twitter followers @indomyfess. The data collection technique used questionnaires distributed online with the help of Google Forms. The data analysis technique in this study uses path analysis with a coefficient of determination. In processing the data, researchers used SPSS version 28. The results showed (1) there was a significant influence between Twitter social media on parasocial relationships with a significance of 0.001 < 0.05, (2) that there was a significant influence between Twitter social media on the level of K-popers trust with a significance value of 0.005 < 0.05, and (3) there is no significant influence between Twitter social media through parasocial relationships on the level of trust of K-popers to the opposite sex. Keywords: Social Media, Twitter, K-Popers, Followers.